Vitamin C Mega Dose vs. Standard Dose in Smokers with Subclinical Hypovitaminosis C, A Controlled Randomized Clinical Trial - a short review (2008)
Smoking induces oxidative stress, which is associated with lower plasma Vitamin C levels. Adult smokers in Bogota, Colombia were randomly recruited into 2 groups, a megadose Vitamin C group (Day 1, 15g IV, Day 2, 15g IV, One gram orally for 2 weeks after) and a standard dose Vitamin C group (Day 1, 100mg IV, Day 2 100mg IV). The study was double blinded. Urine Vitamin C, haemoglobin and haematocrit were measured pre and post intervention in both groups. Results: At the end of the study Haematocrit and Haemoglobin levels were lowered significantly in the megadose group. C-LDL was not significantly different between the groups. Urine Vitamin C was raised in both groups.